Lactiplantibacillus plantarum X7022 ameliorates loperamide‐induced constipation and modulates gut microbiota in mice. Issue 3 (2nd November 2022) - Chen, Xingye; Liu, Guang; Zhao, Li; Du, Lei; Xie, Jingli; Wei, Dongzhi
Abstract: Lactiplantibacillus plantarum X7022 is a novel strain isolated from stinky tofu brine. Its constipation amelioration potential was evaluated on two different constipation types (acute and subacute) in mice induced by loperamide hydrochloride in present work. L. plantarum X7022 could significantly decrease the first black stool defecation time, and increase black fecal weight, number, and the gastrointestinal transit ratio in both models. High‐dose treatment of L. plantarum X7022 (2 × 10 10 CFU/kg BW) was more significant in improving constipation condition than low‐dose (2 × 10 7 CFU/kg BW). Furthermore, 16S rDNA sequencing of the intestinal flora showed that the treatment with the strain X7022 could increase the α diversity in both constipation models. Meanwhile, the abundance of Bacteroidetes increased, and Firmicutes decreased, which was more effective in acute constipated mice. In addition, X7022 treatment could enhance the relative abundance of beneficial flora, such as Bacteroides, Ruminococcus, and depressed Adlercreutzia and Odoribacter in acute model mice. In subacute constipated mice, X7022 treatment could enhance Alloprevotell, Rikenellaceae_RC9, and decreased Lachnospiraceae_NK4A136 and Desulfovibrio . Therefore, L. plantarum X7022 is a prospect probiotic strain for the amelioration of constipation. Abstract : Lactiplantibacillus plantarum X7022 is a novel strain isolated from the traditional fermented stinky tofu brine. L. plantarum X7022 could alleviate constipation by improving defection indices. L. plantarum X7022 regulated gut microbiota dysbiosis in the two different constipation models.